Consumers' willingness to offset their CO2 emissions from traveling: A discrete choice analysis of framing and provider contributions - Claudia Schwirplies; Elisabeth Dütschke; Joachim Schleich; Andreas Ziegler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
This paper identifies potential drivers and individuals' willingness to pay (WTP) for offsetting their emissions from traveling. We focus on the effects of framing the polluting activity with different modes of transportation (i.e. bus and plane) and travel occasions (i.e. holiday and professional training) as well as the effects of contributions from the travel provider. The analyses are based on discrete choice experiments with a representative sample of about 1000 consumers from Germany. Applying mixed logit and latent class logit models, the findings suggest substantial framing effects resulting from the variation in the mode of transportation as well as a significantly higher WTP when offsets are matched by the travel provider 1:1. The findings further indicate that re-/afforestation projects in the participants' region are the preferred mode for compensation. Respondents who are more willing to offset emissions from traveling seem to be younger and female, have a higher income, exhibit stronger environmental and social preferences, and believe that offsetting is effective in protecting the climate.
urn:nbn:de:0011-n-4457835
Keywords: H41; Q54; Q58; 330; climate change; carbon offsetting; framing effects; provider contribution; willingness to pay; discrete choice experiments